Dual-path exploration of anaerobic biotechnology under carbon neutrality goals: from wastewater methane production to systematic utilization of renewable energy - Zhao, Zihan; Chen, Ziwei (Frontiers in Environmental Science, 2025)
This study investigates the application of anaerobic biotechnology in wastewater treatment and resource recovery within the carbon neutrality framework. It systematically elucidates the complete technological chain, from methane production to renewable energy utilization. In the context of intensifying global climate change, carbon neutrality has emerged as a critical strategic objective worldwide. The energy-intensive and high-carbon wastewater treatment sector has become a key focus for emission reduction. Distinct from conventional processes plagued by high energy consumption and carbon emissions, anaerobic biotechnology is garnering increasing attention due to its triple advantages in energy recovery, resource utilization, and emission reduction. By employing anaerobic microorganisms to convert organic matter into methane and other renewable energy sources, this technology not only reduces CO2 emissions but also provides energy supplementation for wastewater treatment facilities. The research further examines specific applications of anaerobic biotechnology in methane synthesis, nutrient recovery from wastewater, and sludge treatment, along with synergistic mechanisms with other renewable energy technologies. While demonstrating significant potential, technology still confronts multifaceted challenges including process optimization, cost management, and social acceptance. Findings confirm that anaerobic biotechnology serves as a vital pathway for low-carbon transformation in wastewater treatment, offering multidimensional value for establishing circular economy systems and advancing sustainable development.